Fiducial marker and marker‐less soft‐tissue detection using fast MV fluoroscopy on a new generation EPID: Investigating the influence of pulsing artifacts and artifact suppression techniques. Issue 10 (25th September 2014) - Poels, Kenneth; Verellen, Dirk; Van de Vondel, Iwein; El Mazghari, Rafik; Depuydt, Tom; De Ridder, Mark
Abstract : Purpose: : Because frame rates on current clinical available electronic portal imaging devices (EPID's) are limited to 7.5 Hz, a new commercially available PerkinElmer EPID (XRD 1642 AP19) with a maximum frame rate of 30 Hz and a new scintillator (Kyokko PI200) with improved sensitivity (light output) for megavolt (MV) irradiation was evaluated. In this work, the influence of MV pulse artifacts and pulsing artifact suppression techniques on fiducial marker and marker‐less detection of a lung lesion was investigated, because target localization is an important component of uncertainty in geometrical verification of real‐time tumor tracking. Methods: : Visicoil™ markers with a diameter of 0.05 and 0.075 cm were used for MV marker tracking with a frame rate of, respectively, 7.5, 15, and 30 Hz. A 30 Hz readout of the detector was obtained by a 2 × 2 pixel binning, reducing spatial resolution. Static marker detection was conducted in function of increasing phantom thickness. Additionally, marker‐less tracking was conducted and compared with the ground‐truth fiducial marker motion. Performance of MV target detection was investigated by comparing the least‐square sine wave fit of the detected marker positions with the predefined sine wave motion. For fiducial marker detection, a Laplacian‐of‐Gaussian enhancement was applied after which normalized cross correlation was used to find the most probable marker position. Marker‐less detection was performed by using the scale and orientation adaptive mean shift tracking algorithm. For each MV fluoroscopy, a free running (FR‐nF) (ignoring MV pulsing during readout) acquisition mode was compared with two acquisition modes intending to reduce MV pulsing artifacts, i.e., combined wavelet‐FFT filtering (FR‐wF) and electronic readout synchronized with respect to MV pulses. Results: : A 0.05 cm Visicoil marker resulted in an unacceptable root‐mean square error (RMSE) > 0.2 cm with a maximum frame rate of 30 Hz during FR‐nF readout. With a 30 Hz synchronized readout (S‐nF) and during 15 Hz readout (independent of readout mode), RMSE was submillimeter for a static 0.05 cm Visicoil. A dynamic 0.05 cm Visicoil was not detectable on the XRD 1642 AP19, despite a fast synchronized readout. For a 0.075 cm Visicoil, deviations of sine wave motion were submillimeter (RMSE < 0.08 cm), independent of the acquisition mode (FR, S). For marker‐less tumor detection, FR‐nF images resulted in RMSE > 0.3 cm, while for MV fluoroscopy in S‐mode RMSE < 0.1 cm for 15 Hz and RMSE < 0.16 cm for 30 Hz. Largest consistency in target localization was experienced during 15 Hz S‐nF readout. Conclusions: : In general, marker contrast decreased in function of higher frame rates, which was detrimental for marker detection success. In this work, Visicoils with a thickness of 0.075 cm were showing best results for a 15 Hz frame rate, while non‐MV compatible 0.05 cm Visicoil markers were not visible on the new EPID with improved sensitivity compared to EPID models based on a Kodak Lanex Fast scintillator. No noticeable influence of pulsing artifacts on the detection of a 0.075 cm Visicoil was observed, while a synchronized readout provided most reliable detection of a marker‐less soft‐tissue structure.